THE PROCESS OF PSYCHOLOGICAL TRAINING OF ATHLETES FOR SPORTS COMPETITIONS - Madumarov Tursunboy Abdukhokimovich; Mukhtarov Davudbek (American Journals, 2024)
Psychological training is a crucial component of an athlete's preparation for competitions. This paper explores the methodologies and strategies involved in enhancing mental resilience, focus, and motivation among athletes. It discusses various psychological techniques and their impact on performance, providing insights into effective practices for coaches and sports psychologists.